FT-IR and GC-MS Analysis of Stem Extract of Ethnomedicinal Plant: Bridelia montana (Roxb.) Willd - Sahithya, S; Krishnaveni, C (Asian Journal of Biological and Life Sciences)
Human beings have been using plants with medicinal properties since so many years in traditional and folk medicine due to the therapeutic potential they possess. Exploration of the plants with medicinal properties has unearthed numerous novel drugs that are used to treat varied human and animal diseases. Bridelia montana (Roxb.) Willd is one of the important ethnomedicinal plants used across the southern part of India. Qualitative analysis of phytochemicals revealed the presence of phenols, glycosides, flavonoids, tannins and carbohydrates. Fourier Transform Infra- Red analysis results showed 5 major peaks and the Gas Chromatography and Mass Spectrometry study revealed the presence of 8 phytocompounds from the stem extract of Bridelia montana. The phytocompounds that were present were identified by the comparison of their peak area percentage and the retention time with the help of library sources and by the mass spectra interpretation. Many of these compounds were used in the pharmaceutical industries for their antimicrobial, antitumor and antioxidant properties.
Keywords: Bridelia montana; FTIR; GCMS; Medicinal plant; Phytochemical analysis